Mineral absorption in relation to nutritional ecology of reindeer - Staaland, H.; Hove, K.; White, R. G. (Rangifer, 1986)
This paper addresses the way which absorption of minerals relate to nutritional ecology and mineral conservation processes. A latin square designed experiment was used to assess the effects of diet on mineral (Ca, Mg, K, Na) absorption processes in reindeer (Rangifer tarandus L.). Three male calves were fed 3 different diets: concentrate with 25% grass meal (RF-71), lichens, and a mixed diet of lichens and RF-71. Two other male calves were fed the lichen or mixed diet, supplemented with 4 g Ca/day. Ca supplementation significantly increased fecal Ca excretion, reduced the excretion of K and Mg, but had no significant effect on Na excretion. Rates of intake and fecal exretion of Ca, Mg and K were highly correlated (P<0.001), while no correlations were found for Na. Negative digestibilities of Ca, Mg and K, and a positive Na digestibility were noted for the lichen diet. For the other diets, all minerals were in positive digestibility, and Ca supplements increased the digestibility of all minerals. Digesta from different sections of the alimentary tract were collected after termination of the experiment. Alimentary pools of Ca and K were equal for animals fed lichen or RF-71, whereas the Na pool was largest on the lichen diet and the Mg pool largest on the RF-71 diet. Rumen turnover time (rumen mineral pool size/daily mineral intake) was consistently less than 3 days for Ca and Mg, but was 22 and 82 days for Na on the RF-71 and lichen diets respectively. Estimates of mineral exchange in various parts of the tract showed that the intestines play and important role in scavanging endogenously secreted minerals. Results are discussed with respect to mineral binding by lichens and the possible role of natural mineral supplements in the nutritional ecology of reindeer.